Biomechanical analysis of All-on-4 implant supported framework using different materials across various clinical practice - Xiaoxuan Chen; Zhengyi Xu; Kuo Gai; Xibo Pei; Ruyi Li; Qianbing Wan (BMC Oral Health)
Abstract Background With the global aging trend, the number of edentulous individuals is steadily increasing. All-on-4 implant restoration can greatly recovery masticatory function in edentulous patients. This study aims to determine the effect of framework material and cantilever length on the stress distribution in All-on-4 implant components using three-dimensional finite element analysis, thereby providing clinicians with insights into the design of All-on-4 superstructures to improve patient outcomes. Methods Five framework models with cantilever lengths of 0 mm, 3 mm, 6 mm, 9 mm, and 12 mm were established, with the cantilever material selected as either titanium (Ti) or polyetheretherketone (PEEK). The jawbone, implant, and framework models were then assembled, with four implants placed in the jawbone according to the classic All-on-4 design and connected to the framework via abutments. Finally, occlusal forces were applied to the framework. Finite element analysis was used to obtain the stress and strain distribution in the jawbones, as well as the stress distribution within the implants and the frameworks. Results Overall, the use of a PEEK framework demonstrated better stress distribution in the jawbone due to its elastic modulus, the maximum stress of which is 26% lower at most than Ti. Although PEEK frameworks showed lower stress overall, implant stress increased, particularly for cantilever lengths over 6 mm, reaching values up to 2.6 times higher than in titanium. Conclusions Cantilever length and framework material are interrelated factors that both influence the stress distribution in the All-on-4 system. A PEEK framework can serve as an alternative to titanium framework in short cantilever lengths (under 6 mm), offering slightly better mandibular protection. Titanium is preferable for lengths between 6 mm and 9 mm to reduce mechanical risk. Cantilever lengths exceeding 12 mm are discouraged due to increased stress. Trial registration Not Applicable.